Determinants of preventive oral health behaviour among senior dental students in Nigeria - Folayan, Morenike O (BioMed Central, 2013)
BACKGROUND: To study the association between oral health behaviour of senior dental students in Nigeria and their gender, age, knowledge of preventive care, and attitudes towards preventive dentistry. METHODS: Questionnaires were administered to 179 senior dental students in the six dental schools in Nigeria. The questionnaire obtained information on age, gender, oral self-care, knowledge of preventive dental care and attitudes towards preventive dentistry. Attending a dental clinic for check-up by a dentist or a classmate within the last year was defined as preventive care use. Students who performed oral self-care and attended dental clinic for check-ups were noted to have complied with recommended oral self-care. Chi-square test and binary logistic regression models were used for statistical analyses. RESULTS: More male respondents agreed that the use of fluoride toothpaste was more important than the tooth brushing technique for caries prevention (P < 0.001). While the use of dental floss was very low (7.3%), more females were more likely to report using dental floss (p=0.03). Older students were also more likely to comply with recommended oral self-care (p<0.001). In binary regression models, respondents who were younger (p=0.04) and those with higher knowledge of preventive dental care (p=0.008) were more likely to consume sugary snacks less than once a day. CONCLUSION: Gender differences in the awareness of the superiority of using fluoridated toothpaste over brushing in caries prevention; and in the use of dental floss were observed. While older students were more likely to comply with recommended oral self-care measures, younger students with good knowledge of preventive dental care were more likely to consume sugary snacks less than once a day.